Contrastes entre estratégias de falantes bilíngues na produção de um diálogo e um monólogo em inglês - Silva, Amaury Flávio (2009)
The purpose of this dissertation is to investigate the strategies used by a group of bilingual speakers in the production of a dialogue and a monologue in English and to analyse a listening activity from a course book. In order to do it, the theoretical background used in the investigations was based on the theories and models about coarticulation found in the book organised by Hardcastle and Hewlett (2002) Coarticulation: Theory, Data and Techniques; The Articulatory Phonology; developed by Browman and Goldstein (1986; 1989; 1990a; b; 1992); and the findings accomplished by Cho (2002) on The Effects of Prosody on Articulation. The production of the dialogue and the monologue were carried out by a group of late bilingual male speakers of English and Portuguese, aged from 18 to 48 years old. So as to carry out the analyses, the PRAAT free software version 4.5.18, developed by Paul Boersma and David Weenink, from the Institute of Phonetic Sciences of the University of Amsterdan was used. The results obtained through the investigations indicated the presence of coarticulatory phenomenona such as hiding in contexts like let me see; blending in almost daily; the presence of the flap in get out; the presence of vowels between consonants in contexts like much better; and so forth. The investigations concerning the course book revealed the fact that the consonants, which according to the course book answer key were not pronounced, were, indeed, pronounced. This was possible through the analyses of the spectrograms of each segmentation